1990
DOI: 10.1088/0953-8984/2/26/007
|View full text |Cite
|
Sign up to set email alerts
|

Thermopower of several ternary compounds of cerium and uranium: CeTX and UTX(T identical to Ni, Pd or Pt; X identical to In or Sn)

Abstract: The authors have measured the thermopower S, from 2 to 300 K, of several ternary compounds of cerium and uranium: CeTX and UTX with T identical to transition metals Ni, Pd or Pt and with X identical to In or Sn. The behaviour of S for these cerium compounds seems to be capable of interpretation as due to the strength of the hybridisation of the Ce-4f electron with conduction electrons. On the other hand, the behaviour of S for the uranium compounds changes enormously for each compound. Prominently sharp peaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 16 publications
1
14
1
Order By: Relevance
“…Transport and magnetic studies of RPtIn intermetallics (R ¼ rare-earth element) revealed interesting physical properties in several members of this family of compounds. CePtIn [7][8][9][10] and YbPtIn [4,11,12] were found to be dense Kondo systems. No magnetic ordering was found down to 60 mK in CePtIn [7,8], whereas YbPtIn was reported to order antiferromagnetically below 3.4 K [11].…”
Section: Introductionmentioning
confidence: 95%
“…Transport and magnetic studies of RPtIn intermetallics (R ¼ rare-earth element) revealed interesting physical properties in several members of this family of compounds. CePtIn [7][8][9][10] and YbPtIn [4,11,12] were found to be dense Kondo systems. No magnetic ordering was found down to 60 mK in CePtIn [7,8], whereas YbPtIn was reported to order antiferromagnetically below 3.4 K [11].…”
Section: Introductionmentioning
confidence: 95%
“…For example, the distorted square 1 ϱ [Ni 2 Sn 2 ] ladder is observed in the Ni-Pt substructure of NP-CePtSn [8] (TiNiSi structure type, [9] Figure 3, a). In NP-CePtSn, the ladders are directly connected to form a three-dimensional network with Ce atoms situated in the cavities.…”
Section: Related Crystal Structuresmentioning
confidence: 99%
“…In NP-CePtSn, the ladders are directly connected to form a three-dimensional network with Ce atoms situated in the cavities. [8] b) Ca 6 Cu 2 Sn 7 , [10] c) SrNiSn 2 , [12] d) Sm 2 NiSn 4 , [13] and e) Yb 3 CoSn 6 . [31] The alkaline earth and rare earth metal atoms are drawn as black spheres, the tetrel and transition-metal atoms as white and grey spheres, respectively.…”
Section: Related Crystal Structuresmentioning
confidence: 99%
“…Magnetic and transport measurements on some of these materials revealed a variety of physical properties across the series: CePtIn (Fujita, 1988;Kurisu, 1999;Yamaguchi, 1990;Satoh, 1990) and YbPtIn (Trovarelli, 2000;Kaczorowski, 2000;Yoshii, 2004) appear to be dense Kondo systems, with the electronic specific heat coefficient y larger than 500 mJ/mol K2, and 430 mJ/rnol K2 respectively; no magnetic order was observed in the former compound down to 60 mK (Satoh, 1990), whereas the latter appears to order antiferromagnetically below 3.4…”
Section: Introductionmentioning
confidence: 99%